FARMING PRACTICE IN A FLOODPLAIN VILLAGE OF ASSAM (INDIA): CONTINUITY AND CHANGE - Nityananda Deka; A. K. Bhagabati (Indonesian Journal of Geography, 2010)
Farming practice in a floodplain environment holds great ecological,economic and social significance. In many cases, agriculture is modernizedwithout caring much for the local environmental conditions. The traditionalfarming practices, although relatively less productive, are more often than not ecofriendlyand sustainable. This paper attempts to study the farming practicesfollowed in a floodplain village of the Brahmaputra valley, Assam, India in termsof cropping practice, inputs and crop protection measures, methods of harvestingand threshing and changes in cropping technology. The study is based on (i)primary data collected from all the 408 households of the village through apurposively designed survey schedule, (ii) interviews with selected farmers andother local knowledgeable persons, and (iii) field observation made by the authors.The data and information thus generated have been summarized using simplestatistical and cartographic tools. The study reveals that the farming practice in thevillage is still traditional in nature with little application of modern inputs andimplements. The small size of landholding and scattering of plots and very limiteddiversification of the rural economy hinder the process of modernization of thefarming practice.